The moral weight of ecology : public goods, cooperative duties, and environmental politics - Tverdek, Edward (Lexington Books, 2015)
The Moral Weight of Ecology: Public Goods, Cooperative Duties, and Environmental Politics is a meticulous examination of the beliefs held by environmentalists and anti-environmentalists alike. It is unique in the "environmental philosophy" genre insofar as it defends positions beholden to neither the mainstream or radical environmental movement nor their libertarian and "free-market" policy counterparts.